Modelagem ambiental na bacia hidrográfica do Rio Poxim-Açu/SE e suas relações antrópicas - Silva, Marinoé Gonzaga da (2013)
Population growth and economic development has led to the unsustainable use of natural resources. The occupation of land often occurs preferentially in areas close to water sources, and frequently proceeds without any a priori planning, resulting in harm to both the availability and quality of water supplies. Hydrological models are widely used to study and predict the hydrosedimentological processes that occur in hydrographic basins, aiding the understanding of changes in water quality and quantity resulting from the use and management of the soil, and enabling prediction of possible alterations in ecosystems. The overall aim of this work was to study the hydrosedimentological dynamics of the hydrographic basin of the Poxim-Açu River, using qualitative and quantitative water monitoring, together with a mathematical model to simulate different scenarios according to the type of land use. The study region comprised the hydrographic basin of the Poxim-Açu River, located in the eastern region of Sergipe State. The SWAT (Soil and Water Assessment Tool) model was used to simulate the production of water, sediments, and nutrients. Water quality monitoring campaigns were conducted on a monthly basis, between February 2010 and March 2011, at 7 stations distributed along the basin. The parameters analyzed were: conductivity, turbidity, color, total dissolved solids, dissolved oxygen, alkalinity and hardness, nutrients (total phosphorus, dissolved orthophosphate, nitrite, nitrate, ammoniacal nitrogen, and total nitrogen), chlorophyll-a, and thermotolerant and total coliforms. Soil samples were collected for the determination of physico-hydric properties: density, humidity, percentages of clay, silt, and sand, macro- and microporosity, total porosity, and infiltration rate. Monitoring of the flow rate and water column height of the Poxim-Açu River was undertaken between July 13 2011 and September 26 2011, using bathymetry and a winch. The water quality in the basin was found to be degraded in terms of the levels of dissolved oxygen and total and thermotolerant coliforms. The soils presented densities in the range 1.07-1.88 g.cm-3 and humidities below 35%. The greatest infiltration rates were obtained for Quartzarenic Neosols, followed by Litholic Neosols, Gleysols, and Red-Yellow Argisols, respectively. The depth-availability curve obtained using polynomial regression showed a high coefficient of determination (R² = 0.9376). After sensitivity analysis and calibration, the model provided satisfactory performance, with values: NSE = 0.77, R² = 0.65, PBIAS = 5.05, RMSE = 0.48, and RSR = 0.49. The validation statistics were poorer than obtained during the calibration procedure, probably due to the small sample size of the flow data. It was found that 30% of the hydrographic basin produced 65% of the sediment, 84% of total nitrogen, 93% of phosphate, and 86% of total phosphorus. These sub-basins were characterized by the presence of Red-Yellow Argisols and Gleysols, with the area occupied by pasture exceeding 40% in all cases, and being greater than 90% in one case (sub-basin 21). The scenario in which the hydrographic basin was occupied by forest showed the lowest values for the production of water, sediments, and nutrients. This was in contrast to the implementation of annual cultivations, such as sugar cane, which greatly increased the production of sediments and nutrients.